Edible Film Characterization from Cassava Starch and Its Organoleptic Properties as Primary Packaging of Snake Fruit Lunkhead - Yeyen Prestyaning Wanita; Purwaningsih Purwaningsih (APTA and DTIP FTP UGM, 2017)
Most of the food packaging material made from plastic, which is difilcult to be decomposed. We need food packaging materials environmentally friendly and edible directly with the product. The experiment was conducted in the laboratory of post-harvest, Yogyakarta AIAT in March to October 2012. The purpose of this study was to know the characteristics of edible film made from cassava starch and organoleptic value as primary packaging of snake fruit lunkhead. The experimental design used was completely randomized design with two factors, nine treatments and three replications. The first factor was the percentage of cassava starch used, the second factor was the type of plasticizer used. The results showed that: 1) The range of water content from the ninth edible film treatments were 10-32%. 2) The highest percentace of cassava starch addition, caused the increassing of edible film water vapor transmission rate. 3) The use of sorbitol plasticizers provides the highest water vapor transmission rate. 4) The range of peroxide content from ninth edible film treatment were 1,64 – 7,08 meq/kg. 5) As the primary packaging snake fruit lunkhead, the highest edible film panelist overall preferences was from sorbitol plasticizer and 4% use of cassava starch, ie. 80% of panelists like it, with an average value 3,8 which means they like it.